Prinses Zonneschijn: ontstaan, analyse en weerklank van een totaalkunstwerk - Forment, Bruno 1978-; Bertels, Kurt (Brussels ASP Editions, 2023)
Those who would like to gain an unbiased idea of Gilson’s skills as operatic composer are out of luck: to date, there does not exist a decent, commercially available recording of Prinses Zonneschijn (‘Princess Sunshine’), the composer’s acknowledged masterpiece in the genre. For want of more reliable auditive sources, one has to content oneself with two incomplete radio recordings from the VRT archives: one of the first act from 1965, conducted by Daniel Sternefeld and supplemented with a disturbing voice-over; and a live recording of a performance with cuts from 1983. A decent edition of the orchestral score might bring solace, but this is not available either; Gilson’s autograph has disappeared without a trace. Fortunately, the library of the Opera Ballet Vlaanderen preserves a series of hitherto ignored treasures: a vocal score in Gilson’s hand; an orchestral score produced by a copyist and annotated in various hands; a complete set of orchestral parts; an annotated libretto with stage directions; and a Repetiteur, being a vocal score in Gilson’s hand with stage directions by the librettist, Pol de Mont.In this essay, we use these and other sources, such as correspondence, iconographic material, archival records and reviews, as raw materials for an archaeological study of Gilson’s opera. Without offering definitive answers to the question whether or not Prinses Zonneschijn constitutes a forgotten masterpiece or an overblown artefact of the Flemish movement, we consider the piece as a multidisciplinary work of art that was produced by different operators: in addition to the composer and librettist, a widely branched, dynamic and anything but unanimous network of directors, set designers, performers, patrons, critics, ... Rereading all these voices and driving forces leads to fresh insights into the underlying stylistic choices of De Mont and Gilson. It also allows us to recognise different layers of meaning in a rich soil of evidence. A first layer pertains to the opera’s genesis: the historical antecedents of De Mont’s libretto and Gilson’s score, both of which are rich in intertextualisms. In the period preceding the creation, De Mont made his way from student environments to the first plan of the Flemish movement. He did pioneering work in folklore, created a fiercely appreciated poetic oeuvre, turned out to be a pangermanist, occasional director and art historian, and was also a driving force in the establishment of the Vlaamse Opera. Prinses Zonneschijn was therefore De Mont’s project in the first place, and Gilson’s to a much lesser extent. The composer, however, coloured De Mont’s story with such an idiosyncratic musical idiom that Prinses Zonneschijn gradually became his opera. Between the Antwerp creation, the French-language production at La Monnaie and the renewed production at the recently completed Vlaamse Opera, the characters of De Mont and Gilson were not only increasingly placed on an equal footing; their artistic collaboration was also enriched in an essential way by the insights of other artists, such as the set designer Albert Dubosq. In that short period, the Princess grew into a symbolist Gesamtkunstwerk, which today can be documented by means of (annotated) libretti, scores, staging manuals, and photographs. The genetic and performative layers generated the sediment for the third layer, laid down between 1907 and 1983: the period in which a flawless, audiovisual fairy tale generated significant resonance, but gradually deteriorated into a vague memory of Flamingantism. Unable to withstand modern opera insights, the Princess silently disappeared from the repertoire, waiting for a new awakening.
FRIS
1
Keywords: Gilson, Paul -- 1865-1942; Resounding Libraries: Unfolding Archived Knowledge Through Artistic Research; Opera; Fairy tale; Music history; Musical analysis; Staging